Geary City, Doniphan County - Laroff, Brannt (Kansas State University, The Chapman Center for Rural Studies, 2015)
This project is over the river town of Geary City located in the Wayne Township of Doniphan County, Kansas. Geary City ultimately lost out because of a transportation issue resulting in the Palermo Railroad never being completed. Methods for the project include family accounts, early plat maps, photographs of Geary City town site, and newspaper articles.
Brannt Laroff, “Geary City, Doniphan County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/161.
Keywords: Brush Creek; Doniphan County; Dr. Edwin H. Grant; Panic of 1857; Pennsylvanians; The Geary City Era